Speed Control of Steel Rolling Mill using Neural Network - Ali, Abduladhem A.; Abdulrahman, Alaa M. (Iraqi Journal for Electrical and Electronic Engineering, 2006)
In this paper a fully neural network-based structure have been proposed to control speeds of rolling stands of a steel rolling mill. The structure has property of controlling the motors speed such that the loop height between each successive stands tracks the required height reference. Synchronization between these stands is also maintained so that the metal flow rate from first stand to the last stand is kept constant. This structure is robust against the disturbance effects such as, torque loading, plant parameter change... etc. The results reveal performance of the structure as a comparison with the conventional control method for a practical worksheet data.